Effect of the Rs2923234 and Rs1049112 Single Nucleotide Polymorphisms of Salivary Acidic Proline-rich Protein on Dental Caries in Young Children: An Analytical Cross-sectional Molecular Study - Maitha Sameer Kadhim; Ahlam Taha Mohammed (Wolters Kluwer Medknow Publications, 2023)
Introduction: We aimed to use polymerase chain reaction (PCR) on genomic deoxyribonucleic acid (DNA) to detect the Db allele and the rs2923234 and rs1049112 single nucleotide polymorphisms (SNPs) of the salivary acidic proline-rich proteins (PRPs) to determine their relationship with dental caries in young children. Methods: DNA was extracted from saliva samples of preschool children aged 3 to 5 years. PCR primers designed around exon 3 of the PRH1 locus yielded a 416-base product representing Db for gel electrophoresis and a 519-base product representing the rs2923234 and rs1049112 SNPs for Sanger sequencing. The data were analyzed using a logistic regression model and a multilayer perceptron artificial neural network. Results: Forty children with severe caries and 40 caries-free children completed the study. The frequency of the Db gene was 16.3% in the entire study group. The rs2923234 SNP was a marginally significant (P = 0.053) predictor for the dependent variable (caries-free or severe caries). However, the rs1049112 (P = 0.407) and the Db allele (P = 0.442) were not significant predictors. Conclusion: The rs29232334 SNP could be considered a potential genetic predictor for caries susceptibility.